Les femmes au sein de la sphère politique cacicale coloniale de la vallée de Copiapo, Royaume du Chili, XVIe siècle - Enrique Cortés Larravide (Nuevo mundo - Mundos Nuevos, 2014)
A number of colonial testimonies refer to a female figure who had great political power among local groups during the period of Spanish/Native contact in the mid-sixteenth century in the valley of Copiapo, south of the Atacama Desert. This figure, called by the Spanish chroniclers Lainacacha, also built significant relationships with Christians during the Hispanic conquest period of the region. Thereafter, her daughter (Ana Quilinachay) seems to have taken over without we knowing whether she had inherited this status because she was the eldest or because she was a woman. She continued to be a very important figure in the valley among the Spaniards. Despite the important role that women played during this period, by the early seventeenth century their memory had already vanished, and many changes had occurred in indigenous leadership. The article examines this exceptional case in the Andean area, where there are very few references on the role of women in the highest levels of local political sphere during the colonial period. The article also analyses the historical, social and territorial dynamics at play during this period when various interests clashed; these dynamics shed light on the reasons that can account for the disappearance of women in the local Aboriginal politics.